Analogy or fallacy, unsafe chemical alternatives: mechanistic insights into energy metabolism dysfunction induced by Bisphenol analogs in HepG2 cells - Jia, Shenglan (2023)
Bisphenol analogs (BPs) are widely used as industrial alternatives for Bisphenol A (BPA). Their toxicity assessment in humans has mainly focused on estrogenic activity, while other toxicity effects and mechanisms resulting from BPs exposure remain unclear. In this study, we investigated the effects of three BPs (Bisphenol AF (BPAF), Bisphenol G (BPG) and Bisphenol PH (BPPH)) on metabolic pathways of HepG2 cells. Results from comprehensive cellular bioenergetics analysis and nontarget metabolomics indicated that the most important process affected by BPs exposure was energy metabolism, as evidenced by reduced mitochondrial function and enhanced glycolysis. Compared to the control group, BPG and BPPH exhibited a consistent pattern of metabolic dysregulation, while BPAF differed from both, such as an increased ATP: ADP ratio (1.29-fold, p < 0.05) observed in BPAF and significantly decreased ATP: ADP ratio for BPG (0.28-fold, p < 0.001) and BPPH (0.45-fold, p < 0.001). Bioassay endpoint analysis revealed BPG/BPPH induced alterations in mitochondrial membrane potential and overproductions of reactive oxygen species. Taken together these data suggested that BPG/BPPH induced oxidative stress and mitochondrial damage in cells results in energy metabolism dysregulation. By contrast, BPAF had no effect on mitochondrial health, but induced a proliferation promoting effect on cells, which might contribute to the energy metabolism dysfunction. Interestingly, BPPH induced the greatest mitochondrial damage among the three BPs but did not exhibit Estrogen receptor alpha (ERα) activating effects. This study characterized the distinct metabolic mechanisms underlying energy metabolism dysregulation induced by different BPs in target human cells, providing new insight into the evaluation of the emerging BPA substitutes.